Pengaruh Dosis Pupuk Kandang Sapi Dan Ukuran Benih Terhadap Pertumbuhan Dan Hasil Tanaman Bawang Merah (Allium Ascalonicum L.) - Katharina Iluminata Uma; Edy Kustiani; Junaidi Junaidi (Universitas Kadiri, 2022)
This study aimed to determine whether there was an interaction between the dose of cow manure and seedling size on the growth and yield of shallots. This research was conducted from April 30â€“ July 2, 2021, at the Green House of the Faculty of Agriculture, Kadiri University. The research method used in this study was a two-factor Completely Randomized Design (CRD) and was repeated 3 times. The first factor was the dose of cow manure (D) which consists of three levels, namely without cow manure (D0), 100 gr/plant (D1), and 200 gr/plant (D2), while the second factor was the size of the seed (U), consisted of three levels, namely U1 (> 3 grams), U2 (3 grams onion 5 grams) and U3 (â‰¥ 5 grams). Parameters observed in this study consisted of plant height, number of leaves, number of tillers, number of tubers, wet weight, and dry weight of tubers. The data were analyzed using the analysis of variance (ANOVA) and if there was a significant effect, it was continued with the Duncan's Range Test (DMRT) at a level of 5%. The results showed that there was an interaction between the dose of cow manure and seedling size on plant height, number of leaves, number of tillers, wet weight, and dry weight of tubers. The dose treatment of cow manure (100 g/plant) had a significant effect on the number of bulbs in shallot plants.